Birds of a feather get misidentified together: High entitativity decreases recognition accuracy for groups of other‐race faces. (21st July 2014) - McGuire, Mollie; Pezdek, Kathy
Abstract : Purpose: The cross‐race effect can be exaggerated when faces are presented in groups, leading to less accurate eyewitness identifications (Pezdek, O'Brien, & Wasson, 2012, Law Hum. Behav ., 36, 488). Our current study examined the effect of entitativity, the degree to which members of a group are perceived as a coherent unit (Campbell, 1958, Behav. Sci ., 3, 14), on recognition accuracy for same‐ and cross‐race faces presented in groups. Methods: White participants viewed 16 slides of 3‐face groups (eight White groups, eight Black groups). Prior to viewing the faces they were told that the entitativity of each 3‐face group was high ('friends who do things together') or low ('people in line at the bank'). They were then tested on 32 individually presented faces (16 old and 16 new). Results: When cross‐race faces were presented in high rather than low entitativity groups, less accurate face recognition memory resulted. Increasing group entitativity decreased recognition accuracy for cross‐race faces but increased recognition accuracy for same‐race faces. Conclusions: The results suggest that the perception of a group negatively impacts eyewitness memory. Contextual factors such as entitativity need to be considered along with other estimator variables when assessing eyewitness identification accuracy.